Gymnasium network educational resource as a form of interactive communication of a teacher and a student - Sidorova N. N., Rudenko E. A. (Interactive science, 2017)
this article presents the experience of the Surgut gymnasium «Laboratory Salahova» teachers in creating a network educational resource on various subjects. Developed course gives students and teachers an opportunity to increase the level of self-employment high-school students and to expand the distance learning in high school. The individual characteristics of every class are considered in the tasks, and this is an advantage of the course developed by the teachers of the gymnasium. The article gives examples of history lesson technological map with assignments and texts proposed for study and already-learned topic check.
Keywords: дистанционное обучение; технология развития критического мышления через чтение и письмо; distance education; cетевой образовательный ресурс; Технология модульного обучения; технология программированного обучения; дистанционная кейс-технология; network educational resource; modular training technology; programmed education technology; reading and writing for critical thinking technology; distance case technology